2019
DOI: 10.2217/pgs-2018-0182
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of HER2 Overexpression on the miRNA and circRNA Transcriptomes in Two Breast Cell Lines and Their Vesicles

Abstract: HER2 upregulation is related with poor outcome in many tumor types. Whereas anti-HER2 treatment is the standard approach as adjuvant therapy in HER2-overexpressing breast cancer, the frequent relapses reinforce the need for alternative treatments. Here we used next-generation sequencing (NGS) to evaluate miRNAs and circRNAs in the cell-lines HB4a and C5.2, where the latter is a HER2-overexpressing clone of the former, and also from two different populations of their secreted extracellular vesicles. Whereas cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Three of them (miR-30d-5p, miR-195-5p, and miR-223-3p) were previously reported to be downregulated in HER2-overexpressing/amplified cancers [22][23][24]. miR-223-3p is also downregulated in HER2-overexpressing C5.2 cell line [25]. Citron et al postulated a central role for miR-223 in the control of epidermal growth factor signaling and HER2 activation, as it reduces the oncogenic potential of HER2-transformed mammary epithelial cells [26].…”
Section: Discussionmentioning
confidence: 94%
“…Three of them (miR-30d-5p, miR-195-5p, and miR-223-3p) were previously reported to be downregulated in HER2-overexpressing/amplified cancers [22][23][24]. miR-223-3p is also downregulated in HER2-overexpressing C5.2 cell line [25]. Citron et al postulated a central role for miR-223 in the control of epidermal growth factor signaling and HER2 activation, as it reduces the oncogenic potential of HER2-transformed mammary epithelial cells [26].…”
Section: Discussionmentioning
confidence: 94%
“…Presence of growth factors leads to heterodimerization and activation of MAPK and PI3K signaling pathways (Graus-Porta et al, 1997). ERBB2 is a proto-oncogene that is overexpressed in approximately 25% of breast cancers, but also in gastric and other cancers, leading to malignant transformation of epithelial cells (Slamon et al, 2011;Fang et al, 2017;Galli de Amorim et al, 2019). Overexpression occurs mostly due to gene amplification, but other activating mutations were also described (Slamon et al, 2011;Galli de Amorim et al, 2019).…”
Section: Erbb2mentioning
confidence: 99%
“…ERBB2 is a proto-oncogene that is overexpressed in approximately 25% of breast cancers, but also in gastric and other cancers, leading to malignant transformation of epithelial cells (Slamon et al, 2011;Fang et al, 2017;Galli de Amorim et al, 2019). Overexpression occurs mostly due to gene amplification, but other activating mutations were also described (Slamon et al, 2011;Galli de Amorim et al, 2019). ERBB2 overexpression is associated with a more aggressive phenotype with worse survival because of increased proliferation, invasiveness and metastasis (Slamon et al, 2011).…”
Section: Erbb2mentioning
confidence: 99%
See 1 more Smart Citation
“…Predicted potential circRNA-miRNA interaction networks showed that hsa-circRNA-0088088 and hsa-circRNA-0005795 might function as ceRNAs and were associated with several cancer-related pathways, such as the Wnt, estrogen, TGF-b, and FoxO signaling pathways (58). Amorim et al presented a nextgeneration sequencing (NGS)-based transcriptome view of the miRNA and circRNA landscape of two breast-derived cell lines, HB4a and C5.2, in the context of HER2 upregulation, demonstrating that identification of hundreds of circRNAs in these cells as well as their exosome-containing EVs (59). Wang identified 5842 DE circRNAs in the MDA-MB-231 cells compared with the MCF-7 cells by cluster analysis (60).…”
Section: Exosomal Circrnasmentioning
confidence: 99%